2021
DOI: 10.3389/fphar.2021.675443
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenation of Helicobacter pylori–Associated Atrophic Gastritis Through Concerted Actions of Placenta-Derived Mesenchymal Stem Cells Prevented Gastric Cancer

Abstract: Chronic Helicobacter pylori infection causes gastric cancer via the progression of precancerous chronic atrophic gastritis (CAG). Therefore, repairing gastric atrophy could be a useful strategy in preventing H. pylori–associated gastric carcinogenesis. Although eradication of the bacterial pathogen offers one solution to this association, this study was designed to evaluate an alternative approach using mesenchymal stem cells to treat CAG and prevent carcinogenesis. Here, we used human placenta-derived mesench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…CAG is a necessary process from gastritis to gastric cancer. The diagnosis, treatment, and monitoring of CAG would effectively prevent the occurrence of gastric cancer [ 12 , 13 ]. Compared with synthetic compounds, this traditional Chinese medicine component has the characteristics of less toxicity and more effects.…”
Section: Discussionmentioning
confidence: 99%
“…CAG is a necessary process from gastritis to gastric cancer. The diagnosis, treatment, and monitoring of CAG would effectively prevent the occurrence of gastric cancer [ 12 , 13 ]. Compared with synthetic compounds, this traditional Chinese medicine component has the characteristics of less toxicity and more effects.…”
Section: Discussionmentioning
confidence: 99%
“…hPMSC, as well as their conditioned medium, were used as a therapeutic approach to atrophic gastritis. Treated animals showed that hPMSC and the conditioned medium significantly reduced inflammation and gastric atrophy, contributing to a reversion to a normal environment and preventing the development of gastric precancerous lesions triggered by Helicobacter pylori [ 32 ].…”
Section: Placenta Cellsmentioning
confidence: 99%
“…PLGC represents a crucial stage in the progression from inflammation to carcinoma in the stomach. Chronic infection with Helicobacter pylori ( H. pylori ) is a significant contributor to the development of GC through the progression of precancerous CAG[ 4 ], emphasizing its role in the inflammation-to-carcinoma transformation in the stomach. Understanding the molecular mechanism underlying H. pylori -induced gastric “inflammation-carcinoma transformation” is essential for identifying new therapeutic targets to effectively intervene in PLGC.…”
Section: Introductionmentioning
confidence: 99%